Motivational Interviewing in a Family-Based Pediatric Obesity Program: A Case Study - Irby, Megan (2010)
Motivational Interviewing (MI) is an effective method for clinicians to guide and support individuals who wish to make complex health behavior changes; however, little research is available to support its use in the treatment of obesity, particularly in family based therapy and multidisciplinary team settings. The objective of this case report is to demonstrate the application of MI within a family based, multidisciplinary treatment program, and provide examples of MI in obesity treatment. We report a case study on the use of MI with behavioral therapy in a pediatric, family based, multidisciplinary weight management program (Brenner FIT Program). Tina, a 14-year-old White female, and her mother participated in the Brenner FIT Program where we successfully integrated MI into her obesity treatment. Further work is needed in the application of MI to diverse care teams to determine frequency of training required for effective use of MI in obesity treatment, its limitations, and its feasibility in community-based programs.